FOLTIC METHODE TO IMPROVING THE PERFORMANCE OF VEGETABLE SKIN - Tutik Maryati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
This article explains the foltik method for improving the performance of vegetable skin. This is important in order to increase knowledge of developing one's own creativity. Through the foltic technique of folding and giving color to vegetable leather, it will improve the appearance of vegetable leather, cover skin defects with color and add unique value to vegetable leather. Folding vegetable skin by emphasizing artistic value when applying color will be the key to the success of the foltic method. Articles are not carried out by research but are approached and reviewed by journals, both national and international. The appearance of vegetable leather with a natural, plain color, with minimal defects can be changed and the appearance of the leather can be enhanced to become colored leather with a combination of dyestuff colors. Various color patterns according to the folding of the skin will add unique value, artistry, creativity to a technician in increasing the selling value of vegetable leather by improving the appearance of vegetable leather which is liked by consumers.